Pendampingan Pengolahan Data Penerima Bantuan Sosial di Kelurahan Taba Koji Lubuklinggau - lestari, raniyah ayu; Putra, Mardiansyah; Dalilah, Dina (Journal of Social Responsibility Projects by Higher Education Forum, 2024)
Community service can be done through various ways, such as providing services to the community, community empowerment, developing community skills and abilities, and disseminating science and technology to the community. This activity can involve lecturers, students, and other related parties. Assistance in processing data on social assistance recipients in Taba Koji Village, Lubuklinggau City aims to assist the community in managing and processing data related to the receipt of social assistance. In this assistance, lecturers have the duty to assist the community in data processing, provide training, supervise and provide input, assist in data analysis, and assist in the preparation of reports. Through this assistance, it is hoped that the community can have a better understanding of data processing and the results can be used to perencanaan program bantuan sosial di Kelurahan Taba Koji, bersifat manual sehingga proses pengambilan keputusan menjadi tidak akurat, lama, dan bersifat objektif. Oleh karena itu, diperlukan solusi berupa sistem pendukung pengambilan keputusan agar dapat memproses bantuan data masyarakat lebih cepat dan akurat menggunakan kriteria yang ada.